2012
DOI: 10.1097/ico.0b013e31823f0977
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Factors of Meibomian Gland Dysfunction

Abstract: MGD was highly prevalent in this Asian population and associated with various systemic and ocular conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
69
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 22 publications
4
69
1
6
Order By: Relevance
“…This association, which has also been reported in other population-based studies, 22 must not be explained by a selection bias in male participation, as the low proportion of males in the sample derives not only from a true difference in sex distribution in the population of reference but also from the nonproportionate sampling method used in this study, with the same number of subjects in each stratum. In agreement with clinic-based studies, 23 which tend to select symptomatic patients, no association was found with respect to symptoms (as if a factor increased the symptoms threshold in males or diminished it in females).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This association, which has also been reported in other population-based studies, 22 must not be explained by a selection bias in male participation, as the low proportion of males in the sample derives not only from a true difference in sex distribution in the population of reference but also from the nonproportionate sampling method used in this study, with the same number of subjects in each stratum. In agreement with clinic-based studies, 23 which tend to select symptomatic patients, no association was found with respect to symptoms (as if a factor increased the symptoms threshold in males or diminished it in females).…”
Section: Discussionmentioning
confidence: 54%
“…20,21 Siak et al 22 found no age differences in a population-based study performed in Singapore. It is conceiv-able that a genetic predisposition of Asians to MGD might determine the high prevalence rates across all age groups observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[63,79-82] Population-based studies indicate that Asians have higher prevalence of MGD, ranging from 60.8% to 69.3% in those aged over 40 years. [83] However, two large population-based studies on Caucasians aged 40 to 97 years, revealed prevalence rates from 3.5% to 19.9%.…”
Section: Methods and Limitations In The Diagnosis And Treatment Of Mementioning
confidence: 99%
“…8 In comparison, the Singapore Malay Eye Study reported a 56% MGD prevalence (defined as either meibomian gland orifice plugging or lid margin telangiectasia in at least one eye). 9 Other studies in Asian countries have similarly reported high prevalence estimates ranging from 39% to 68%, each using a different definition of MGD. 1015 In clinic based studies and likewise using different definitions, MGD prevalence estimates range from 32% to 78% (Table 2).…”
Section: Introductionmentioning
confidence: 93%